1998
DOI: 10.1117/12.324068
|View full text |Cite
|
Sign up to set email alerts
|

PMMA development studies using various synchrotron sources and exposure conditions

Abstract: PMMA has been the primary resist used in synchrotron exposures for micro-machined parts fabricated by the LIGA process. Because development ofthis resist directly influences both tolerances and surface fmish ofcompleted LIGA structures, it is important to have a good quantitative understanding of PMMA development as a function ofthe absorbed dose, as well as both the exposure and development conditions. The various synchrotron sources used for LIGA fabrication vary widely in beam energy and flux, and these var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…These values are based on a non-linear least-squares fit of Eq. (9) to a large set of measured development rates [13]. This correlation also agrees reasonably well with development rates previously measured by others [14].…”
Section: Development Processsupporting
confidence: 86%
“…These values are based on a non-linear least-squares fit of Eq. (9) to a large set of measured development rates [13]. This correlation also agrees reasonably well with development rates previously measured by others [14].…”
Section: Development Processsupporting
confidence: 86%
“…The constants G, B, and p are chosen as 12.3 (lm/min), 8.44 kJ/cm 3 , and 3.81 to provide a best fit to the data reported by Pantenburg et al [11] for T ¼ 21 C and for doses that span the range used in the examples treated below. These values are somewhat different than those used by Tan et al [10] to fit a data set that extends to higher doses. The activation energy is typically on the order of 140 kJ/mol, but this is of no importance to our examples as they are limited to cases with T ¼ T 0 ¼ 21 C. In a quasi-steady development process the recession rate, dh=dt, is proportional to the net dissolution rate, Rðq s À q l C b Þ, which must be in balance with the rate of fragment transport from the development surface into the bath, q l DShDC=h [12].…”
mentioning
confidence: 77%
“…Previous studies of the kinetics have shown that the dissolution rate of PMMA in a GG developer fluid may be well approximated by the expression [10].…”
mentioning
confidence: 99%
“…The parameters a, b and c for GG developer are 13.6 lm/min, 4.6 kJ/cm 3 , and 3.8 respectively, for all synchrotron sources. Additional details of the exposure and development models have been reported previously [4,5]. These exposure and development models are coupled in a user-friendly code known as LEX-D.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Kinetic-limited development rates normally depend on the development temperature and local total dose [4], but may additionally depend on the dose rate and mean photon energy of the dose. In our general development model, the kinetic rate is computed from the PMMA molecular weight after the dose.…”
Section: Numerical Modelmentioning
confidence: 99%